A Developing World Rejoinder to Children's Rights, Deinstitutionalisation and the Development of Foster Care. Issue 3 (27th May 2022) - Islam, Tuhinul; Fulcher, Leon
Abstract : Harlow ( Practice : 1–13, 2021) argued for the development of foster care world-wide, potentially funded through the closure of residential institutions. This rejoinder highlights a selective literature review in these arguments, along with comparative research challenges. Social work career paths rarely traverse between family case work and residential or looked after care practices, thereby influencing professional perspectives. Assumptions about universal access to primary and secondary education in the Developing World are unfounded, as are assumptions about availability of community health and welfare services in local communities world-wide. Because residential care homes are largely operated in Developing World countries by local benefactors or rely on donations with little, if any, support from the state, it follows that closure of children's homes will not release funds for the support of families and foster care. Cross-cultural, and religious differences require careful consideration to account for meanings, use and acceptability of Western notions of foster care operating in the Developing World as well as in multi-cultural UK cities.